Associations of drinking water and urinary uranium with incident diabetes among U.S. adults: The Multi-Ethnic Study of Atherosclerosis and the Strong Heart Family Study - Maya Spaur; Kathrin Schilling; Ronald A. Glabonjat; Anirban Basu; Kevin P. Patterson; Wil Lieberman-Cribbin; Qixuan Chen; Filippo Ravalli; Marta Galvez-Fernandez; Pam Factor-Litvak; Steven Chillrud; Benjamin C. Bostick; et al. (Environmental Research, 2026)

Acorn woodpeckers alter resource use, group size, and spring productivity across an urban landscape - Olivia R. Knapp; Kendra E. Forster; Alexander J. Rurik; Isabelle Hugoniot; Eric S. Reyes; Peter B. Schramm; Corban A. Muthiah; Aaron Wong; Seth C. Wilmoth; Sophia L. McRae; Caleb Courson; Theodore J. Patterson; et al. (Urban Ecosystems, 2026)
Access to suitable resources shapes the evolution and maintenance of avian cooperative breeding by influencing whether an individual will have a greater chance of survival and reproduction by dispersing or remaining on a natal territory. Cooperatively-breeding species exhibit altered dispersal according to food availability and habitat quality, but the relationship between resource use, group size, and reproduction in human-altered landscapes remains to be studied. We examined how urbanization, key resource availability, and resource use relate to differences in group size and number of offspring in an urban population of facultative cooperatively-breeding acorn woodpeckers. Acorn woodpeckers shifted to increased use of ornamental trees, palms, and anthropogenic structures for granaries in more urbanized areas and where oak trees, a key historic food and granary resource, are in lower abundance and proximity. Pair breeding was more prevalent in urbanized areas and seemed to be primarily associated with use of utility poles for granaries. In general, territories with utility poles as granaries and higher urbanization levels hosted smaller group sizes. In contrast, while the number of fledglings was higher in larger groups, it did not vary with urban resources when controlling for group size. Our findings suggest that land conversion levels and the relative availability of historic and novel resources shape habitat quality, resulting in differing patterns of group living and subsequent productivity across the urban landscape. This indicates that while novel resources may enable wildlife to occupy urban areas, they may also influence the social behavior of facultative cooperative breeders.

Ancestry informative genetic variants associated with tobacco metabolic and detoxification capacity measured by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) among smokers - Oladimeji Lanade; Zhongxuan He; Yan Zhou; Elizabeth Blackman; Denise Gibbs; Sharon Harrison; Karthik Devarajan; Mark Andrake; Roland L. Dunbrack; Gerald Nkogbu; Aditi Wagh; Michael Slifker; et al. (Archives of Toxicology, 2026)
Tobacco use remains the leading preventable cause of cancer mortality worldwide, with marked disparities in cancer incidence and outcomes across racial and ethnic groups. This study investigates the genetic determinants of tobacco carcinogen metabolism among smokers, focusing on ancestry-informative markers (AIMs) near genes involved in metabolic activation (Phase I), detoxification (Phase II), and transport (Phase III) of tobacco-specific carcinogens. Using data from 274 smokers recruited in the United States and the Caribbean, we measured urinary NNAL (a metabolite of NNK) to classify metabolic phenotypes and performed genotyping with a customized array enriched for AIMs. Most participants (94%) were classified as poor metabolizers of NNAL, with a higher prevalence among Black/African American smokers. Multivariable analyses, after adjusting for age, sex, assay batch, and number of cigarettes smoked per day, identified 14 AIMs near Phase I, II, and III pathway genes significantly associated with NNAL metabolizer phenotype, with African ancestry alleles conferring increased odds of poor metabolism. Functional annotation revealed that most significant AIMs overlapped regulatory regions, and the CYP3A5 rs776746 variant demonstrated structural disruption likely to impair enzymatic activity. Majority of participants had high African ancestry and were poor NNAL metabolizers, consistent with the observed association between African ancestry and poor NNAL metabolism. These findings highlight the biological basis for tobacco-related cancer disparities and underscore the importance of integrating genetic ancestry and metabolic phenotyping in risk assessment and personalized prevention strategies for tobacco-associated cancers.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Challenges and solutions in measuring commonly used biomarkers for drug-induced liver injury in a liver-on-a-chip platform - Qiang Shi; Laura K. Schnackenberg; Lijun Ren; Katy S. Papineau; Jessica J.H. Oliphant; Mark I. Avigan; Lorna Ewart; John FK. Sauld; Emily Dai; Paul C. Brown; Karen L. Davis Bruno; Frederic Moulin; et al. (Toxicology Letters, 2025)

Exploring Breastfeeding Professionals’ Perspectives on Artificial Intelligence for Breastfeeding Support - C. Tranchina; A. MacMillan Uribe; S. Econie; H. Jetel; J. Patterson (Journal of the Academy of Nutrition and Dietetics, 2025)

Evaluating Informational Quality of AI-bot Generated Outputs for Common Breastfeeding Questions - H. Jetel; J. Patterson; C. Tranchina; S. Econie; A. MacMillan Uribe (Journal of the Academy of Nutrition and Dietetics, 2025)

Comprehensibility of Artificial Intelligence Chatbot Responses for Common Breastfeeding Questions - S. Econie; A. MacMillan Uribe; H. Jetel; C. Tranchina; J. Patterson (Journal of the Academy of Nutrition and Dietetics, 2025)

Edible Campus: Empowering Students Through Integrated Campus Gardening and Meal Preparation Programs - J. Lefaver; C. Starr; D. Folliard; B. Flower; J. Patterson; M. Duffrin (Journal of the Academy of Nutrition and Dietetics, 2025)

Birds of a Feather Self-Regulate Together: The Intersection of Peer Networks and Self-Regulated Learning in Biomedical Engineering - Linlin Luo; Joseph C. Tise; Megan S. Patterson; Daniel L. Alge; Paul R. Hernandez (Biomedical Engineering Education, 2025)

Spatiotemporal Dynamics of Non‐Ecological Speciation in Rubyspot Damselflies ( Hetaerina spp.) - C. Patterson; A. Brennan; H. Cowling; A. González‐Rodríguez; G. F. Grether; L. Mendoza Cuenca; M. Springer; Y. M. Vega‐Sánchez; J. Drury (Molecular Ecology, 2025)
Non‐ecological speciation is a common mode of speciation, which occurs when allopatric lineages diverge in the absence of pronounced ecological differences. Yet, relative to other speciation mechanisms, non‐ecological speciation remains understudied. Numerous damselfly clades are characterised as non‐adaptive radiations (the result of several rounds of non‐ecological speciation without subsequent divergence), but there are few damselfly lineages for which we have a detailed understanding of the spatiotemporal dynamics of divergence. Recent phylogeographic analyses demonstrate that American rubyspot damselflies ( Hetaerina americana sensu lato) actually comprise at least two cryptic lineages that coexist sympatrically across most of Mexico. To broaden our understanding of the dynamics of diversification to other rubyspot lineages, we investigated the phylogeographic history of smoky rubyspot damselflies ( Hetaerina titia ) using genomic data collected across Central and North America. Unexpectedly, we found evidence of reproductive isolation between the highly genetically differentiated Pacific and Atlantic lineages of H. titia in a narrow secondary contact zone on the Isthmus of Tehuantepec, Mexico. We then fit models of historical demography to both H. americana sensu lato and H. titia to place these comparisons in a temporal context. Our findings indicate that Pacific and Atlantic lineages of H. titia split more recently than the broadly sympatric lineages within H. americana sensu lato, supporting key assumptions of the non‐ecological speciation model and demonstrating that these two pairs of sister lineages are at different stages of the speciation cycle.

Call for neurofibromatosis specialty care clinics in South Carolina - Camerun C. Washington; Kenya M. De Leon; Jessica A. Cooley Coleman; Wesley G. Patterson; Michael J. Lyons (Journal of Community Genetics, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Bomb 14C validates Gray Triggerfish (Balistes capriscus) dorsal spine and otolith ageing protocols - Derek W. Chamberlin; Jennifer C. Potts; Walter D. Rogers; Zachary A. Siders; William F. Patterson (Fisheries Research, 2024)

Difference in Dietary Behaviors Between Children with and Without Neurodevelopmental Disabilities: Results from the 2022 National Survey of Children’s Health - S. Robson; L. Krott; C. Baker-Smith; A. Bhat; F. Patterson; B. Brewer (Journal of the Academy of Nutrition and Dietetics, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Estimating reductions in the risk of vessels striking whales achieved by management strategies - Jessica V. Redfern; Brooke C. Hodge; Daniel E. Pendleton; Amy R. Knowlton; Jeffrey Adams; Eric M. Patterson; Caroline P. Good; Jason J. Roberts (Biological Conservation, 2024)

A review of bats of the genus Pseudoromicia (Chiroptera: Vespertilionidae) with the description of a new species - Amanda L. Grunwald; Terrence C. Demos; Yvette Nguéagni; Martin N. Tchamba; Ara Monadjem; Paul W. Webala; Julian C. Kerbis Peterhans; Bruce D. Patterson; Luis A. Ruedas (Systematics and Biodiversity, 2023)

Effects of urbanization on the efficiency and composition of vertebrate scavengers - Jessica R. Patterson; Nicolas Szabo; James C. Beasley (Food Webs, 2023)

Ultraconserved elements resolve phylogenetic relationships and biogeographic history of African-Malagasy bent-winged bats (Miniopterus) - Terrence C. Demos; Paul W. Webala; Steven M. Goodman; Julian C. Kerbis Peterhans; Holly L. Lutz; Bernard R. Agwanda; Natalia Cortés-Delgado; Stefania Briones; Richard H. Ree; Bruce D. Patterson (Molecular Phylogenetics and Evolution, 2023)

Evidence of population-level impacts and resiliency for Gulf of Mexico shelf taxa following the Deepwater Horizon oil spill - William F. Patterson; Kelly Lynn Robinson; Beverly K. Barnett; Matthew D. Campbell; David C. Chagaris; Jeffrey P. Chanton; Kendra L. Daly; David S. Hanisko; Frank J. Hernandez; Steven A. Murawski; Adam G. Pollack; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The goal of this paper was to review the evidence of population-level impacts of the Deepwater Horizon Oil Spill (DWH) on Gulf of Mexico (GOM) continental shelf taxa, as well as evidence of resiliency following the DWH. There is considerable environmental and biological evidence that GOM shelf taxa were exposed to and suffered direct and indirect impacts of the DWH. Numerous assessments, from mesocosm studies to analysis of biopsied tissue or tissue samples from necropsied animals, revealed a constellation of physiological effects related to DWH impacts on GOM biota, some of which clearly or likely resulted in mortality. While the estimated concentrations of hydrocarbons in shelf waters and sediments were orders of magnitude lower than measured in inshore or deep GOM environments, the level of mortality observed or predicted was substantial for many shelf taxa. In some cases, such as for zooplankton, community shifts following the spill were ephemeral, likely reflecting high rates of population turnover and productivity. In other taxa, such as GOM reef fishes, impacts of the spill are confounded with other stressors, such as fishing mortality or the appearance and rapid population growth of invasive lionfish ( Pterois spp.). In yet others, such as cetaceans, modeling efforts to predict population-level effects of the DWH made conservative assumptions given the species’ protected status, which post-DWH population assessments either failed to detect or population increases were estimated. A persistent theme that emerged was the lack of precise population-level data or assessments prior to the DWH for many taxa, but even when data or assessments did exist, examining evidence of population resiliency was confounded by other stressors impacting GOM biota. Unless efforts are made to increase the resolution of the data or precision of population assessments, difficulties will likely remain in estimating the scale of population-level effects or resiliency in the case of future large-scale environmental catastrophes.

Investigation of an expanded, lumped-element model of electropenetrography (EPG) and the accuracy of the traditional R and emf model - Elaine A. Backus; William C. (Chip) Patterson (Computers and Electronics in Agriculture, 2023)

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

Warfarin Overdose in an Adolescent Not Dependent on Anticoagulation: Reversal Strategy and Kinetics - C. James Watson; Michael D. Simpson; James D. Whitledge; Al Patterson; Michele M. Burns (Journal of Medical Toxicology, 2022)

Reimagining Sustainable Community Sports Fields of the Future: a Framework for Convergent Science-Stakeholder Decision-Making - C. M. Straw; B. P. McCullough; C. Segars; B. Daher; M. S. Patterson (Circular Economy and Sustainability, 2022)

Episodic Ataxia Type 1: Natural History and Effect on Quality of Life - Tracey D. Graves; Robert C. Griggs; Brian N. Bundy; Joanna C. Jen; Robert W. Baloh; Michael G. Hanna; Joanna J. Jen; Anthony A. Amato; Richard J. Barohn; Angelika F. Hahn; Kimberly Hart; Barbara Herr; et al. (The Cerebellum, 2022)
Episodic ataxia type 1 (EA1) is a rare autosomal potassium channelopathy, due to mutations in KCNA1 . Patients have childhood onset of intermittent attacks of ataxia, dizziness or imbalance. In order to quantify the natural history of EA1, its effect on quality of life and in preparation for future clinical trials, we set up an international multi-centre study of EA1. We recruited thirty-three participants with EA1: twenty-three completed 1-year follow-up and eighteen completed 2-year follow-up. There was very little accumulation of disability or impairment over the course of the 2 years of the study. The outcome measures of ataxia (SARA and functional rating of ataxia) and the activities of daily living scale were largely stable over time. Self-reported health-related quality of life (SF-36) scores were lower across all domains than controls, in keeping with a chronic condition. Physical subdomain scores appeared to deteriorate over time, which seems to be driven by the female participants in the study. This is an interesting finding and warrants further study. Attacks of EA1 reported by participants in real time via an interactive voice response system showed that symptoms were not stereotyped; however, attack duration and frequency was stable between individuals. This large prospective study is the first ever completed in subjects with EA1. We document the natural history of the disorder over 2 years. These data will enable the development of outcome measures for clinical trials of treatment.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Bycatch of a Critically Endangered Shark Glyphis glyphis in a Crab Pot Fishery: Implications for Management - Richard D. Pillans; Gary C. Fry; Geoff D. Carlin; Toby A. Patterson (Frontiers in Marine Science, 2022)
The speartooth shark Glyphis glyphis is a Critically Endangered whaler shark known from a few tropical river systems in northern Australia and Papua New Guinea. There is limited genetic exchange in populations residing in northern Australian rivers that are greater than 100 km apart. In Queensland, the species is only found in the Wenlock and Ducie River that flow into Port Musgrave. Juveniles are confined to upstream reaches of these rivers with seasonal downstream movement related to freshwater influx. This region also supports commercial and recreational fisheries including crab pot and gillnet fisheries. Being obligate ram-ventilators, entrapment in crab pots results in mortality of bycaught speartooth sharks after a few hours. Following anecdotal reports of juvenile speartooth sharks being captured in crab pots, we investigated catch rates in crab pots experimentally and examined commercial fishing effort in the Wenlock and Ducie River from logbook data. Twenty four juvenile (55–80 cm TL) speartooth sharks were captured in experimental crab pots in the Ducie River and Tentpole Creek (a tributary of the Wenlock River) with catch rates high; up to 0.82 (±1.86 SD) sharks pot –1 day –1 . Experimental catch rates in crab pots varied between rivers and with distance upstream and were highest in areas of highest shark density based on detection of acoustically tagged sharks over 7 years and line fishing catch per unit effort data. Although commercial crab effort varies spatially and temporally in relation to current catch rates and market demands, consistent monthly overlap with juvenile speartooth shark core distribution occurred throughout the year. Using CPUE data multiplied by fishing effort in Tentpole Creek, we estimate that in November alone, between 51 and 279 speartooth sharks are potentially captured in years with high fishing effort. Bycatch of juvenile speartooth sharks in commercial and recreational crab pots poses a significant threat to this genetically isolated and small population. Urgent management intervention to drastically reduce bycatch mortality either through gear modifications or spatial closures are required to ensure the viability of this population.

Using an integrative research approach to improve fish migrations in regulated rivers: a case study on Pacific Salmon in the Seton River, Canada - Nolan N. Bett; Scott G. Hinch; Arthur L. Bass; Douglas C. Braun; Nicholas J. Burnett; Matthew T. Casselman; Steven J. Cooke; S. Matthew Drenner; Ahmed Gelchu; William L. Harrower; Roxx Ledoux; Andrew G. Lotto; et al. (Hydrobiologia, 2022)

A first genetic assessment of the newly introduced Isle Royale gray wolves (Canis lupus) - Samuel D. Hervey; Linda Y. Rutledge; Brent R. Patterson; Mark C. Romanski; John A. Vucetich; Jerrold L. Belant; Dean E. Beyer; Seth A. Moore; Kristin E. Brzeski (Conservation Genetics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Effects of early life adversity on maternal effort and glucocorticoids in wild olive baboons - Sam K. Patterson; Katie Hinde; Angela B. Bond; Benjamin C. Trumble; Shirley C. Strum; Joan B. Silk (Behavioral Ecology and Sociobiology, 2021)

Residency, home range and tidal habitat use of Green Turtles (Chelonia mydas) in Port Curtis, Australia - Richard D. Pillans; Gary C. Fry; Michael D. E. Haywood; Wayne Rochester; Colin J. Limpus; Toby Patterson; Russel C. Babcock (Marine Biology, 2021)

Big in the tropics: Ecogeographical clines in peccary size reveal the converse of Bergmann’s rule - Carla Deonisia Hendges; Bruce D. Patterson; Nilton C. Cáceres (Journal of Biogeography, 2021)
Aim Bergmann's rule is an ecogeographical rule that describes a negative relationship between body size and temperature. Here, we used a multivariate measure of skull size (centroid size) as a proxy for body size to test the influence of temperature, precipitation, elevation, human influence and competition on size in Dicotyles tajacu and Tayassu pecari . Location American tropics and sub‐tropics. Taxon Tayassuidae. Methods Using geometric morphometric methods, we measured 426 adult skulls of both peccary species from 174 different localities south of the equator and 83 in the north. We explored the effects of temperature, precipitation, altitude and human influence, controlling for spatial autocorrelation, using ordinary least squares models and the Akaike information criterion. Size differences where the species occur allopatrically or sympatrically, where competition could be a factor, were investigated using ANCOVA models. Results We found that peccaries were larger in the tropics. Temperature and precipitation explained the size variation of both peccaries in the southern hemisphere, whereas human influence is a predictor of size only for T . pecari . Size variation of northern D . tajacu is mainly explained by elevation and temperature. Tayassu pecari is consistently larger than D . tajacu in both hemispheres. Peccaries did not exhibit significant shifts in either rate of change in size or size–latitude relationships between allopatric and sympatric areas. Main conclusions Geographical variation in size of these peccaries does not support Bergmann's rule. In the tropics, precipitation and human influence appear to exert strong selective pressures on body size of peccaries, whose resource utilization patterns are shaped by group living. Size differences of the two species across the continents may contribute to their stable coexistence via interference rather than exploitative competition.

Elevated Calf Mortality and Long-Term Responses of Wild Bottlenose Dolphins to Extreme Climate Events: Impacts of Foraging Specialization and Provisioning - Janet Mann; Vivienne Foroughirad; Molly H. F. McEntee; Madison L. Miketa; Taylor C. Evans; Caitlin Karniski; Ewa Krzyszczyk; Eric M. Patterson; John C. Strohman; Megan M. Wallen (Frontiers in Marine Science, 2021)
As demands for wildlife tourism increase, provisioning has become a popular means of providing up-close viewing to the public. At Monkey Mia, Shark Bay, Australia, up to five adult female Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) visit a 100 m stretch of beach daily to receive fish handouts. In 2011, a severe marine heatwave (MHW) devastated seagrass and fish populations in Shark Bay. Offspring survival declined precipitously among seagrass specialists (dolphins that forage disproportionately in seagrass habitat). As all provisioned dolphins at the site are seagrass specialists, we examined how provisioned and non-provisioned seagrass specialists responded to the MHW. Using 27 years of data we compare habitat use, home range size, calf mortality, and predation risk between provisioned and non-provisioned females and their offspring before and after the MHW. Our results show that provisioned females have extremely small home ranges compared to non-provisioned females, a pattern attributable to their efforts to remain near the site of fish handouts. However, weaned offspring (juveniles) born to provisioned females who are not provisioned themselves also had much smaller home ranges, suggesting a persistent maternal effect on their behavior. After the MHW, adult females increased their use of seagrass habitats, but not their home range size. Provisioned females had significantly lower calf mortality than non-provisioned females, a pattern most evident pre-MHW, and, in the first 5 years after the MHW (peri-MHW, 2011–2015), calf mortality did not significantly increase for either group. However, the ecosystem did not recover, and post-MHW (2016–2020), calf mortality was substantially higher, regardless of provisioning status. With few survivors, the impact of the MHW on juvenile mortality post-weaning is not known. However, over three decades, juvenile mortality among offspring of provisioned vs. non-provisioned females did not statistically differ. Thus, the survival benefits accrued to calves in the provisioned group likely cease after weaning. Finally, although shark attack rates on seagrass specialists did not change over time, elevated predation on calves cannot be ruled out as a cause of death post-MHW. We discuss our results as they relate to anthropogenic influences on dolphin behavioral plasticity and responses to extreme climate events.

Dredging Impacts on Soil Properties of the Kankakee River System 150 Years after Perturbation - Jack V. Ferrara; Joshua J. Puhlick; Tamatha A. Patterson; Katherine C. Glover (Wetlands, 2020)

A Hope-Based Intervention to Address Disrupted Goal Pursuits and Quality of Life Among Young Adult Cancer Survivors - Carla J. Berg; Robin C. Vanderpool; Betelihem Getachew; Jackelyn B. Payne; Meghan F. Johnson; Yasmeni Sandridge; Jennifer Bierhoff; Lana Le; Rakiyah Johnson; Amber Weber; Akilah Patterson; Sarah Dorvil; et al. (Journal of Cancer Education, 2020)

Environmental Influences on Long-term Movement Patterns of a Euryhaline Elasmobranch (Carcharhinus leucas) Within a Subtropical Estuary - R. D. Pillans; G. C. Fry; A. D. L. Steven; T. Patterson (Estuaries and Coasts, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Evidence of diverse movement strategies and habitat use by white sharks, Carcharodon carcharias, off southern Australia - Russell Bradford; T. A. Patterson; P. J. Rogers; R. McAuley; S. Mountford; C. Huveneers; R. Robbins; A. Fox; B. D. Bruce (Marine Biology, 2020)
Large endothermic pelagic sharks are highly migratory and use habitats spanning a broad range of coastal, neritic and oceanic areas. This study aimed to resolve the current lack of information on the movements and habitat use of white sharks, Carcharodon carcharias , between shelf, slope and oceanic areas located off southwestern Australia. Movement behaviours, spatial distribution patterns and vertical habitat use of juvenile, sub-adult and adult white sharks ranging in size from 1.9 to 5.7 m total length were examined using 43 satellite tags deployed over 15 years. Pop-up satellite archival tags and satellite-linked radio tags collected 3663 days and > 109,900 km of tracking data over periods of up to 381 days. We demonstrated sex-based differences in movement and distribution patterns of male (21) and female (19) white sharks. Female dispersal was broader and extended further offshore than males, which largely remained in neritic and gulf habitats. Female white sharks experienced a narrower range of water temperatures ( F = 9.0–19.0 °C; M = 10.4–24.8 °C). Despite these subtle differences, both sexes showed an affinity to the Neptune Island Group and the shelf slope canyons of the eastern Great Australian Bight, which are productive and oceanographically complex regions that support known prey of white sharks. This study highlighted that the southern-western Australian population of white sharks use off-shelf habitat to a greater extent than previously identified. Findings have potential implications for: ecological risk assessments of fisheries that operate in these offshore habitats and for monitoring and managing marine protected areas.

Coming to Terms With Living Shorelines: A Scoping Review of Novel Restoration Strategies for Shoreline Protection - Carter S. Smith; Morgan E. Rudd; Rachel K. Gittman; Emily C. Melvin; Virginia S. Patterson; Julianna J. Renzi; Emory H. Wellman; Brian R. Silliman (Frontiers in Marine Science, 2020)

Multilocus phylogeny of a cryptic radiation of Afrotropical long‐fingered bats (Chiroptera, Miniopteridae) - Terrence C. Demos; Paul W. Webala; Holly L. Lutz; Julian C. Kerbis Peterhans; Steven M. Goodman; Natalia Cortés‐Delgado; Michael Bartonjo; Bruce D. Patterson (Zoologica Scripta, 2020)
The Old World bat family Miniopteridae comprises only the genus Miniopterus , which includes 20 currently recognized species from the Afrotropical realm and 15 species from Eurasia and Australasia. Since 2003, the number of recognized Miniopterus species has grown from 19 to 35, with most newly described species endemic to Madagascar and the Comoros Archipelago. We investigated genetic variation, phylogenetic relationships and clade membership in Miniopterus focusing on Afrotropical taxa. We generated mitochondrial cytochrome‐ b (cyt‐ b ) and nuclear intron data (five genes) from 352 vouchered individuals collected at 78 georeferenced localities. Including 99 additional mitochondrial sequences from GenBank, we analysed a total of 25 recognized species. Mitochondrial genetic distances among cyt‐ b ‐supported clades averaged 9.3%, representing as many as five undescribed species. Multilocus coalescent delimitation strongly supported the genetic isolation of eight of nine tested unnamed clades. A large number of sampled clades in sub‐Saharan Africa are distributed wholly or partly in East Africa (nine of 13 clades), suggesting that Miniopterus diversity has been grossly underestimated. Although 25 of 27 cyt‐ b and 23 of 25 nuclear gene tree lineages from the Afrotropics were strongly supported as monophyletic, a majority of deep nodes were poorly resolved in phylogenetic analyses. Long terminal branches subtending short backbone internodes in the phylogenetic analyses suggest a rapid radiation model of diversification. This hypothesis needs to be tested using more phylogenetically informative data.

NASA’s satellite laser ranging systems for the twenty-first century - J. F. McGarry; E. D. Hoffman; J. J. Degnan; J. W. Cheek; C. B. Clarke; I. F. Diegel; H. L. Donovan; J. E. Horvath; M. Marzouk; A. R. Nelson; D. S. Patterson; R. L. Ricklefs; et al. (Journal of Geodesy, 2019)

Movement responses to environment: fast inference of variation among southern elephant seals with a mixed effects model - I. D. Jonsen; C. R. McMahon; T. A. Patterson; M. Auger‐Méthé; R. Harcourt; M. A. Hindell; S. Bestley (Ecology, 2019)
Like many species, movement patterns of southern elephant seals ( Mirounga leonina ) are being influenced by long‐term environmental change. These seals migrate up to 4,000 km from their breeding colonies, foraging for months in a variety of Southern Ocean habitats. Understanding how movement patterns vary with environmental features and how these relationships differ among individuals employing different foraging strategies can provide insight into foraging performance at a population level. We apply new fast‐estimation tools to fit mixed effects within a random walk movement model, rapidly inferring among‐individual variability in southern elephant seal environment–movement relationships. We found that seals making foraging trips to the sea ice on or near the Antarctic continental shelf consistently reduced speed and directionality (move persistence) with increasing sea‐ice coverage but had variable responses to chlorophyll a concentration, whereas seals foraging in the open ocean reduced move persistence in regions where circumpolar deep water shoaled. Given future climate scenarios, open‐ocean foragers may encounter more productive habitat but sea‐ice foragers may see reduced habitat availability. Our approach is scalable to large telemetry data sets and allows flexible combinations of mixed effects to be evaluated via model selection, thereby illuminating the ecological context of animal movements that underlie habitat usage.

Correction to: DNA barcoding significantly improves resolution of invasive lionfish diet in the Northern Gulf of Mexico - Kristen A. Dahl; William F. Patterson; Alison Robertson; Alice C. Ortmann (Biological Invasions, 2018)

Feeding ecology of invasive lionfish (Pterois volitans and Pterois miles) in the temperate and tropical western Atlantic - Jonathan Peake; Alex K. Bogdanoff; Craig A. Layman; Bernard Castillo; Kynoch Reale-Munroe; Jennifer Chapman; Kristen Dahl; William F. Patterson III; Corey Eddy; Robert D. Ellis; Meaghan Faletti; Nicholas Higgs; et al. (Biological Invasions, 2018)

Temporal and spatial differences in smolting among Oncorhynchus nerka populations throughout fresh and seawater migration - Marley C. Bassett; David A. Patterson; J. Mark Shrimpton (Journal of Fish Biology, 2018)
Physiological changes that occur in the spring are preparatory for salmonid smolts to successfully enter seawater, but variation is likely to exist within species with a wide geographic distribution. Whether differences in development of seawater tolerance exist among populations that differ in distance to the ocean, temporally during the spring, or as fish migrate downstream is not known. Juvenile sockeye salmon Oncorhynchus nerka from four regions in the Fraser River catchment, British Columbia, were intercepted to assess physiological differences among populations and at different times during migration to characterize the parr–smolt transformation. Pre‐migratory fish had low levels of gill Na + –K + ‐ATPase (NKA) activity. High gill NKA activities were observed at the start of migration for some populations, but smolts leaving the lake did not consistently have higher gill NKA activity than non‐migratory juvenile O. nerka sampled in their natal lakes. Gill NKA activity was highly variable at the start of migration with no relationship with distance from the ocean. Gill NKA activity changes with migration were also highly variable, but consistently smolts in the ocean had the highest enzyme activities. Internal and external factors may influence this variation, but the dynamic nature of smolting was not based on the region of origin, timing during migration or on the year of migration.

The effects of disproportional load contributions on quantifying vegetated filter strip sediment trapping efficiencies - Heather E. Gall; Daniel Schultz; Tamie L. Veith; Sarah C. Goslee; Alfonso Mejia; Ciaran J. Harman; Cibin Raj; Paul H. Patterson (Stochastic Environmental Research and Risk Assessment, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Factors affecting estimates of size at age and growth in grey triggerfish Balistes capriscus from the northern Gulf of Mexico - R. J. Allman; W. F. Patterson; C. L. Fioramonti; A. E. Pacicco (Journal of Fish Biology, 2018)
Growth zones in dorsal spines of grey triggerfish Balistes capriscus from the northern Gulf of Mexico were utilized to estimate growth and examine factors that may affect estimates of size at age. Age was estimated from dorsal‐spine sections of 4687 individuals sampled from U.S. waters during 2003–2013, including both fishery‐independent ( n = 1312) and fishery‐dependent ( n = 3375) samples. Ninety‐six per cent ( n = 4498) of these sections were deemed suitable for ageing; average per cent error between two independent readers was 10·8%. Fork length ( L F ) ranged from 65 to 697 mm and age estimates from 0 to 14 years. Both sex and sample source (fishery‐independent v . recreational) significantly affected estimated size at age for 2–6 year‐old fish. Data were pooled between sources to fit sex‐specific von Bertalanffy growth functions. Results for the female model were L ∞ = 387 mm L F , k = 0·52 year −1 and t 0 = 0·01 year, while for males L ∞ = 405 mm L F , k = 0·55 year −1 and t 0 = 0·02 year. These results were significantly different between sexes and indicate clear sexual dimorphism. Thus, growth should be modelled separately by sex when examining population parameters or conducting stock assessment modelling. The positive bias in estimates of size at age computed for recreational v . fishery‐independent samples also has clear implications for stock assessment as growth functions computed with fishery‐dependent samples would tend to overestimate stock productivity.

Boundary Judgments in Water Governance: Diagnosing Internal and External Factors that Matter in a Complex World - Rob C. de Loë; James J. Patterson (Water Resources Management, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

DNA barcoding significantly improves resolution of invasive lionfish diet in the Northern Gulf of Mexico - Kristen A. Dahl; William F. Patterson; Alison Robertson; Alice C. Ortmann (Biological Invasions, 2017)

Novel mutations involving βI-, βIIA-, or βIVB-tubulin isotypes with functional resemblance to βIII-tubulin in breast cancer - Weiwei Wang; Hangxiao Zhang; Xumin Wang; Jordan Patterson; Philip Winter; Kathryn Graham; Sunita Ghosh; John C. Lee; Christos D. Katsetos; John R. Mackey; Jack A. Tuszynski; Gane Ka-Shu Wong; et al. (Protoplasma, 2017)

Mesophotic Coral Ecosystems: A Geoacoustically Derived Proxy for Habitat and Relative Diversity for the Leeward Shelf of Bonaire, Dutch Caribbean - Arthur C. Trembanis; Alexander L. Forrest; Bryan M. Keller; Mark R. Patterson (Frontiers in Marine Science, 2017)

Does maternal captivity of wild, migratory sockeye salmon influence offspring performance? - N. M. Sopinka; C. T. Middleton; D. A. Patterson; S. G. Hinch (Hydrobiologia, 2016)

The Kraken in the Aquarium: Questions that Urgently Need to be Addressed in Order to Advance Marine Conservation - John A. Cigliano; Amy Bauer; Megan M. Draheim; Melissa M. Foley; Carolyn J. Lundquist; Julie-Beth McCarthy; Katheryn W. Patterson; Andrew J. Wright; E. C. M. Parsons (Frontiers in Marine Science, 2016)

Using watershed characteristics to inform cost-effective stream temperature monitoring - Douglas C. Braun; John D. Reynolds; David A. Patterson (Aquatic Ecology, 2015)

Physiological management of dietary deficiency in n-3 fatty acids by spawning Gulf killifish (Fundulus grandis) - Joshua T. Patterson; Christopher C. Green (Fish Physiology and Biochemistry, 2015)

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Thermal regime, predation danger and the early marine exit of sockeye salmon Oncorhynchus nerka - P. J. Katinic; D. A. Patterson; R. C. Ydenberg (Journal of Fish Biology, 2015)
Marine exit timing of sockeye salmon Oncorhynchus nerka populations on the Haida Gwaii Archipelago, British Columbia, Canada, is described, with specific focus on Copper Creek. Marine exit in Copper Creek occurs > 130 days prior to spawning, one of the longest adult freshwater residence periods recorded for any O. nerka population. Copper Creek presents an easy upstream migration, with mild water temperatures (7 to 14° C), short distance (13·1 km) and low elevation gain (41 m) to the lake where fish hold prior to spawning. An energetic model estimates that O.nerka streams in Haida Gwaii has ever exceeded the presumed temperature threshold (19° C) for early marine exit. Although it is not impossible that the thermal tolerance of Copper Creek O.nerka is very low, the data presented here appear inconsistent with thermal avoidance as an explanation for the early marine exit timing in Copper Creek and in three other populations on the archipelago with early marine exit.

Data Quality and the Comparative Method: The Case of Primate Group Size - Samantha K. Patterson; Aaron A. Sandel; Jordan A. Miller; John C. Mitani (International Journal of Primatology, 2014)

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

Hepatic Transcriptome Profiles Differ Among Maturing Beef Heifers Supplemented with Inorganic, Organic, or Mixed (50 % Inorganic:50 % Organic) Forms of Dietary Selenium - James C. Matthews; Zhi Zhang; Jennifer D. Patterson; Phillip J. Bridges; Arnold J. Stromberg; J. A. Boling (Biological Trace Element Research, 2014)

Middle to late Holocene chironomid-inferred July temperatures for the central Northwest Territories, Canada - Lindsay M. Upiter; Jesse C. Vermaire; R. Timothy Patterson; Carley A. Crann; Jennifer M. Galloway; Andrew L. Macumber; Lisa A. Neville; Graeme T. Swindles; Hendrik Falck; Helen M. Roe; Michael F. J. Pisaric (Journal of Paleolimnology, 2014)

Mother knows best, even when stressed? Effects of maternal exposure to a stressor on offspring performance at different life stages in a wild semelparous fish - N. M. Sopinka; S. G. Hinch; C. T. Middleton; J. A. Hills; D. A. Patterson (Oecologia, 2014)

Incorporating Climate and Ocean Change into Extinction Risk Assessments for 82 Coral Species - RUSSELL E. BRAINARD; MARISKA WEIJERMAN; C. MARK EAKIN; PAUL MCELHANY; MARGARET W. MILLER; MATT PATTERSON; GREGORY A. PINIAK; MATTHEW J. DUNLAP; CHARLES BIRKELAND (Conservation Biology, 2013)
Many marine invertebrate species facing potential extinction have uncertain taxonomies and poorly known demographic and ecological traits. Uncertainties are compounded when potential extinction drivers are climate and ocean changes whose effects on even widespread and abundant species are only partially understood. The U.S. Endangered Species Act mandates conservation management decisions founded on the extinction risk to species based on the best available science at the time of consideration—requiring prompt action rather than awaiting better information. We developed an expert‐opinion threat‐based approach that entails a structured voting system to assess extinction risk from climate and ocean changes and other threats to 82 coral species for which population status and threat response information was limited. Such methods are urgently needed because constrained budgets and manpower will continue to hinder the availability of desired data for many potentially vulnerable marine species. Significant species‐specific information gaps and uncertainties precluded quantitative assessments of habitat loss or population declines and necessitated increased reliance on demographic characteristics and threat vulnerabilities at genus or family levels. Adapting some methods (e.g., a structured voting system) used during other assessments and developing some new approaches (e.g., integrated assessment of threats and demographic characteristics), we rated the importance of threats contributing to coral extinction risk and assessed those threats against population status and trend information to evaluate each species’ extinction risk over the 21st century. This qualitative assessment resulted in a ranking with an uncertainty range for each species according to their estimated likelihood of extinction. We offer guidance on approaches for future biological extinction risk assessments, especially in cases of data‐limited species likely to be affected by global‐scale threats. Incorporación del Cambio Climático y Oceánico en Estudios de Riesgo de Extinción para 82 Especies de Coral

Does among‐population variation in burst swimming performance of sockeye salmon Oncorhynchus nerka fry reflect early life migrations? - N. M. Sopinka; S. G. Hinch; A. G. Lotto; C. K. Whitney; D. A. Patterson (Journal of Fish Biology, 2013)
Using a fixed‐speed test, burst swimming performance was found to vary among nine populations of emergent sockeye salmon Oncorhynchus nerka fry reared in a common‐garden environment. No consistent relationship was, however, detected between difficulty of fry migration (upstream v . downstream) to rearing areas and total burst swimming duration or bursting rate.

Individual Intake of Free-Choice Mineral Mix by Grazing Beef Cows May Be Less Than Typical Formulation Assumptions and Form of Selenium in Mineral Mix Affects Blood Se Concentrations of Cows and Their Suckling Calves - Jennifer D. Patterson; Walter R. Burris; James A. Boling; James C. Matthews (Biological Trace Element Research, 2013)

Prostate specific membrane antigen produces pro-angiogenic laminin peptides downstream of matrix metalloprotease-2 - Rebecca E. Conway; Kyle Joiner; Alex Patterson; David Bourgeois; Robert Rampp; Benjamin C. Hannah; Samantha McReynolds; John M. Elder; Hannah Gilfilen; Linda H. Shapiro (Angiogenesis, 2013)

Diggin′ on U(biquitin): A Novel Method for the Identification of Physiological E3 Ubiquitin Ligase Substrates - Carrie E. Rubel; Jonathan C. Schisler; Eric D. Hamlett; Robert M. DeKroon; Mathias Gautel; Oscar Alzate; Cam Patterson (Cell Biochemistry and Biophysics, 2013)

Conserving large carnivores: dollars and fence - C. Packer; A. Loveridge; S. Canney; T. Caro; S.T. Garnett; M. Pfeifer; K.K. Zander; A. Swanson; D. MacNulty; G. Balme; H. Bauer; C.M. Begg; et al. (Ecology Letters, 2013)
Conservationists often advocate for landscape approaches to wildlife management while others argue for physical separation between protected species and human communities, but direct empirical comparisons of these alternatives are scarce. We relate African lion population densities and population trends to contrasting management practices across 42 sites in 11 countries. Lion populations in fenced reserves are significantly closer to their estimated carrying capacities than unfenced populations. Whereas fenced reserves can maintain lions at 80% of their potential densities on annual management budgets of $500 km −2 , unfenced populations require budgets in excess of $2000 km −2 to attain half their potential densities. Lions in fenced reserves are primarily limited by density dependence, but lions in unfenced reserves are highly sensitive to human population densities in surrounding communities, and unfenced populations are frequently subjected to density‐independent factors. Nearly half the unfenced lion populations may decline to near extinction over the next 20–40 years.

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Provenance matters: thermal reaction norms for embryo survival among sockeye salmon Oncorhynchus nerka populations - C. K. Whitney; S. G. Hinch; D. A. Patterson (Journal of Fish Biology, 2013)
Differences in thermal tolerance during embryonic development in Fraser River sockeye salmon Oncorhynchus nerka were examined among nine populations in a controlled common‐garden incubation experiment. Forcing embryonic development at an extreme temperature (relative to current values) of 16° C, representing a future climate change scenario, significantly reduced survival compared to the more ecologically moderate temperature of 10° C (55% v . 93%). Survival at 14° C was intermediate between the other two temperatures (85%). More importantly, this survival response varied by provenance within and between temperature treatments. Thermal reaction norms showed an interacting response of genotype and environment (temperature), suggesting that populations of O. nerka may have adapted differentially to elevated temperatures during incubation and early development. Moreover, populations that historically experience warmer incubation temperatures at early development displayed a higher tolerance for warm temperatures. In contrast, thermal tolerance does not appear to transcend life stages as adult migration temperatures were not related to embryo thermal tolerance. The intra‐population variation implies potential for thermal tolerance at the species level. The differential inter‐population variation in thermal tolerance that was observed suggests, however, limited adaptive potential to thermal shifts for some populations. This infers that the intergenerational effects of increasing water temperatures may affect populations differentially, and that such thermally mediated adaptive selection may drive population, and therefore species, persistence.

The physiological consequences of catch‐and‐release angling: perspectives on experimental design, interpretation, extrapolation and relevance to stakeholders - S. J. Cooke; M. R. Donaldson; C. M. O'connor; G. D. Raby; R. Arlinghaus; A. J. Danylchuk; K. C. Hanson; S. G. Hinch; T. D. Clark; D. A. Patterson; C. D. Suski (Fisheries Management and Ecology, 2013)
Over the past 20 years, there has been a dramatic increase in the use of physiological tools and experimental approaches for the study of the biological consequences of catch‐and‐release angling practices for fishes. Beyond simply documenting problems, physiological data are also being used to test and refine different strategies for handling fish such that stress is minimised and survival probability maximised, and in some cases, even for assessing and facilitating recovery post‐release. The inherent sensitivity of physiological processes means that nearly every study conducted has found some level of – unavoidable – physiological disturbance arising from recreational capture and subsequent release. An underlying tenet of catch‐and‐release studies that incorporate physiological tools is that a link exists between physiological status and fitness. In reality, finding such relationships has been elusive, with further extensions of individual‐level impacts to fish populations even more dubious. A focus of this article is to describe some of the challenges related to experimental design and interpretation that arise when using physiological tools for the study of the biological consequences of catch‐and‐release angling. Means of overcoming these challenges and the extrapolation of physiological data from individuals to the population level are discussed. The argument is presented that even if it is difficult to demonstrate strong links to mortality or other fitness measures, let alone population‐level impacts of catch‐and‐release, there remains merit in using physiological tools as objective indicators of fish welfare, which is an increasing concern in recreational fisheries. The overarching objective of this paper is to provide a balanced critique of the use of physiological approaches in catch‐and‐release science and of their role in providing meaningful information for anglers and managers.

Erratum to: Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Red snapper management in the Gulf of Mexico: science- or faith-based? - J. H. Cowan; C. B. Grimes; W. F. Patterson; C. J. Walters; A. C. Jones; W. J. Lindberg; D. J. Sheehy; W. E. Pine; J. E. Powers; M. D. Campbell; K. C. Lindeman; S. L. Diamond; et al. (Reviews in Fish Biology and Fisheries, 2011)

High Performance Thin Layer Chromatography (HPTLC) profile of an insecticidal compound of Trochus radiatus and assessment of mucus-associated bacterial extracts - Mary Elizabeth K. Gnanambal; K. C. Ramya Devi; P. Hareesh Chandra; Edward J. K. Patterson (Phytoparasitica, 2011)

Efficacy of caspofungin as salvage therapy for invasive aspergillosis compared to standard therapy in a historical cohort - J. W. Hiemenz; I. I. Raad; J. A. Maertens; R. Y. Hachem; A. J. Saah; C. A. Sable; J. A. Chodakewitz; M. E. Severino; P. Saddier; R. S. Berman; D. M. Ryan; M. J. DiNubile; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

A new high-latitude record for the macaroni penguin (Eudyptes chrysolophus) at Avian Island, Antarctica - K. B. Gorman; E. S. Erdmann; B. C. Pickering; P. J. Horne; J. R. Blum; H. M. Lucas; D. L. Patterson-Fraser; W. R. Fraser (Polar Biology, 2010)

Coral disease following massive bleaching in 2005 causes 60% decline in coral cover on reefs in the US Virgin Islands - J. Miller; E. Muller; C. Rogers; R. Waara; A. Atkinson; K. R. T. Whelan; M. Patterson; B. Witcher (Coral Reefs, 2009)

The influence of maternal condition on offspring performance in sockeye salmon Oncorhynchus nerka - K. B. Tierney; D. A. Patterson; C. J. Kennedy (Journal of Fish Biology, 2009)
Eggs were taken from adult sockeye salmon Oncorhynchus nerka that had reached their journey's end in spawn‐ready and moribund condition, and fertilized by healthy males. Egg number, size, hatching success and offspring growth did not differ with maternal condition, which suggests the absence of any persisting physiological maternal effects. Differences were noted in the swimming behaviour and physiology of the offspring at parr stage. In a 30 min schooling test conducted using groups of five in a flume, parr from moribund females were more likely to fatigue, were not as tightly schooled, and had a diminished startle response, both in the per cent responding and the burst distance. In individual, confined swimming tests conducted within a tube, post‐exercise plasma lactate concentration, which is an indicator of white muscle use, was greater for parr from moribund adult females. The moribund females also had elevated lactate following exercise (their migration), which suggests heritable differences may exist in muscle use. This study shows that juvenile O. nerka artificially propagated from females exhausted by their return migration can exhibit swimming performance differences, indicating that maternal condition may need to be considered in breeding programmes.

The conspecific nature of eastern and red wolves: conservation and management implications - C. J. Kyle; A. R. Johnson; B. R. Patterson; P. J. Wilson; B. N. White (Conservation Genetics, 2008)

Jack Edgar Myers (1913–2006), an algal physiologist par excellence - Jerry J. Brand; David W. Krogmann; C. O. Patterson (Photosynthesis Research, 2008)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

Impact of Soil Amendments on Broccoli Quality and Napropamide Movement Under Field Conditions - G. F. Antonious; M. A. Patterson; J. C. Snyder (Bulletin of Environmental Contamination and Toxicology, 2005)

Genomics of plant cell wall biogenesis - Weidong Yong; Bruce Link; Ronan O’Malley; Jagdish Tewari; Charles T. Hunter; Chung-An Lu; Xuemei Li; Anthony B. Bleecker; Karen E. Koch; Maureen C. McCann; Donald R. McCarty; Sara E. Patterson; et al. (Planta, 2005)

Brain mitochondrial injury in human immunodeficiency virus–seropositive (HIV+) individuals taking nucleoside reverse transcriptase inhibitors - Brian C Schweinsburg; Michael J Taylor; Omar M Alhassoon; Raul Gonzalez; Gregory G Brown; Ronald J Ellis; Scott Letendre; John S Videen; J Allen McCutchan; Thomas L Patterson; Igor Grant; the HNRC Group (Journal of NeuroVirology, 2005)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

The reproducibility of closed-pouch sweat collection and thermoregulatory responses to exercise?heat stress - Gavin Hayden; Helen C. Milne; Mark J. Patterson; Myra A. Nimmo (European Journal of Applied Physiology, 2004)

The effect of exercise and captivity on energy partitioning, reproductive maturation and fertilization success in adult sockeye salmon - D. A. Patterson; J. S. Macdonald; S. G. Hinch; M. C. Healey; A. P. Farrell (Journal of Fish Biology, 2004)
Releasing a population of adult Fraser River sockeye salmon Oncorhynchus nerka from an energetically more expensive non‐feeding natural migration (1089 km, natal groups) and allowing them to sexually mature in either a moderate flow (captive exercise group) or a no flow (captive non‐exercise group) environment resulted in significant differences in body energy densities (MJ kg −1 ) among groups (ranked: initial natural migrator > non‐exercise > exercise > natal arrivals). Similarly, per cent body lipids were significantly lower in exercise females compared with non‐exercise females, experimentally confirming the central role lipid catabolism has in powering swimming. Although restricting exercise did result in greater body energy reserves at spawning, this did not result in a reallocation of energy to reproduction, as fecundity, egg size and gonad composition were unchanged among the groups. Furthermore, non‐exercise females had delayed maturity, lower egg deposition rates, and were more likely to die prior to egg ovulation than exercise females and natal spawners. Eggs from captive exercise adult females were more likely to survive to the eyed stage than eggs from captive non‐exercise females, but both captive groups had significantly lower egg fertilization success than natal spawners suggesting that confinement stress played a role in some of results presented. There were no significant differences in plasma levels of glucose, lactate, cortisol and reproductive hormones among the groups, but correlations among acute and chronic indicators of stress were significant among individuals. These results indicate that exercise during the late stages of maturation, as might occur normally, may be required for optimizing reproductive maturation and maximizing reproductive success.

Improved high-throughput sunflower and cotton genomic DNA extraction and PCR fidelity - Erin C. Horne; Siva P. Kumpatla; Koni A. Patterson; Manju Gupta; Steven A. Thompson (Plant Molecular Biology Reporter, 2004)

Pesticide Residues in Soil and Quality of Potato Grown with Sewage Sludge - G. F. Antonious; M. A. Patterson; J. C. Snyder (Bulletin of Environmental Contamination and Toxicology, 2003)

Patterns of spread of coral disease in the Florida Keys - James W. Porter; Phillip Dustan; Walter C. Jaap; Kathryn L. Patterson; Vladimir Kosmynin; Ouida W. Meier; Matthew E. Patterson; Mel Parsons (Hydrobiologia, 2001)

A taxon-specific oligonucleotide probe for temperate zone soil isolates of Glomus mosseae - P. D. Millner; W. W. Mulbry; S. L. Reynolds; C. A. Patterson (Mycorrhiza, 1998)

Simulation of the effect of methane bubble plumes on vertical mixing in Mono Lake - Jos R. Romero; John C. Patterson; John M. Melack (Aquatic Sciences, 1996)

Location and geometric description of carpal bones in CT images - H. D. Tagare; K. W. Elder; D. M. Stoner; R. M. Patterson; C. L. Nicodemus; S. F. Viegas; G. R. Hillman (Annals of Biomedical Engineering, 1993)

The equine major plasma serpin multigene family: Partial characterization including sequence of the reactive-site regions - Scott D. Patterson; Kevin Bell; Denis C. Shaw (Biochemical Genetics, 1991)

The equine major plasma serpin multigene family: Partial characterization including sequence of the reactive-site regions - Scott D. Patterson; Kevin Bell; Denis C. Shaw (Biochemical Genetics, 1991)

Modelling the effects of motion on primary production in the mixed layer of lakes - John C. Patterson (Aquatic Sciences, 1991)

Drosophila purine auxotrophy: New alleles ofadenosine2 exhibiting a complex visible phenotype - S. Y. K. Tiong; C. Keizer; D. Nash; J. Bleskan; D. Patterson (Biochemical Genetics, 1989)

Simulation of bubble plume destratification systems in reservoirs - John C. Patterson; Jorg Imberger (Aquatic Sciences, 1989)

Mapping of bovine PRGS and PAIS genes in hybrid somatic cells: Syntenic conservation with human chromosome 21 - James C. McAvin; David Patterson; James E. Womack (Biochemical Genetics, 1988)

Structure elucidation of some minor components of the polybromobiphenyl mixture, Firemaster - Donna L. Orti; Robert H. Hill; Donald G. Patterson; Larry L. Needham; Renate D. Kimbrough; Cynthia C. Alley; Hsing -Chung J. Lee (Archives of Environmental Contamination and Toxicology, 1983)

Song repertoires and sexual selection in the Red-winged Blackbird - K. Yasukawa; J. L. Blank; C. B. Patterson (Behavioral Ecology and Sociobiology, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Sectional notes - C. H. Metzger; E. R. Bennett; W. B. Ward; J. G. Richard; Ralph W. Donaldson; T. M. Patterson; L. Harris; Marx Koehnke; J. M. Jenkins; W. H. Martin; Robert Schmidt; E. M. Gillig; et al. (American Journal of Potato Research, 1937)

Sectional notes - Louis Soffcke; Julian C. Miller; Frank W. Hussey; E. L. Newdick; T. M. Patterson; Robert Schmidt; D. M. James (American Journal of Potato Research, 1937)